2015
DOI: 10.1016/j.brainres.2015.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Classic and novel stem cell niches in brain homeostasis and repair

Abstract: Neural stem cells (NSCs) critical for the continued production of new neurons and glia are sequestered in distinct areas of the brain called stem cell niches. Until recently, only two forebrain sites, the subventricular zone (SVZ) of the anterolateral ventricle and the subgranular zone (SGZ) of the hippocampus, have been recognized adult stem cell niches (Alvarez-Buylla and Lim, 2004; Doetsch et al., 1999a, 1999b; Doetsch, 2003a, 2003b; Lie et al., 2004; Ming and Song, 2005). Nonetheless, the last decade has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 221 publications
5
78
0
Order By: Relevance
“…More recently, the hypothalamus has been identified as a third important neurogenic area in the mammalian brain [12,13] (see Figure I in Box 1).…”
Section: Adult Neurogenesismentioning
confidence: 99%
“…More recently, the hypothalamus has been identified as a third important neurogenic area in the mammalian brain [12,13] (see Figure I in Box 1).…”
Section: Adult Neurogenesismentioning
confidence: 99%
“…It has been suggested that CT-1 levels within CSF are controlled by a release mechanism dependent on CP dynamics and structural integrity. CP have been sometimes considered as a circumventricular organs (CVOs) [64] containing potential niches of stem/precursor cells that can be activated by injury [65,66]. In line with this observation, Ochiai and coworkers demonstrated that CT-1 was able to signal in fetal neuroepithelial cells (also called neuron stem cells, NSC, in the early-gestational to mid-gestational stages) and to induce premature astrocyte formation in cultured cortical precursors in a synergistic manner with bone morphogenetic protein (BMP)-2 via a gp130-JAK-STAT3 pathway.…”
Section: Nervous Systemmentioning
confidence: 99%
“…It is currently accepted that a combination of niche signals and cell intrinsic programs orchestrate the transition from an undifferentiated stem cell state to a progenitor cell committed to the final fate. Among multiple sources of adult stem cells, neural SCs (NSCs) and mesenchymal SCs (MSCs) have been intensively studied for their role in brain and bone physiology as well as for their potential use in cell-based therapies for treating neurological/neurodegenerative diseases and for reconstructive surgery, respectively (Yamaguchi, 2014; Hayrapetyan et al, 2015; Lin and Iacovitti, 2015). …”
Section: Introductionmentioning
confidence: 99%